Pengaruh Kualitas Produk dan Citra Merek terhadap Keputusan Pembelian Konsumen Pada Rumah Makan Pondok Kayuan - Muhammad Amin; Muhajirin; Sri Ernawati (CV Edujavare Publishing, 2026)
This study aims to examine the influence of product quality and brand image on consumer purchasing decisions at Pondok Kayuan Restaurant. The research employed a quantitative approach using a survey method. Primary data were collected through questionnaires distributed to consumers of Pondok Kayuan Restaurant and analyzed using multiple linear regression with the assistance of SPSS software. Prior to hypothesis testing, the research instrument was evaluated through validity, reliability, and classical assumption tests to ensure the accuracy and feasibility of the regression model. The findings indicate that product quality has a positive and significant effect on consumer purchasing decisions. Factors such as taste, cleanliness, freshness of ingredients, food presentation, and consistency of quality were found to play an important role in encouraging consumers to make purchases. Furthermore, brand image also has a positive and significant effect on purchasing decisions, suggesting that a positive reputation, strong brand identity, and consumer trust contribute to increasing consumers' intention to purchase. Simultaneously, product quality and brand image significantly influence purchasing decisions, with a coefficient of determination (R²) of 0.890. This result indicates that 89% of the variation in purchasing decisions can be explained by these two independent variables, while the remaining 11% is influenced by other factors outside the scope of this study. Therefore, improving product quality and strengthening brand image are essential strategies for increasing consumer purchasing decisions and enhancing the competitiveness of Pondok Kayuan Restaurant.